1988
DOI: 10.1016/0022-0728(88)80270-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in real surface area, crystallographic orientation and morphology of platinum electrodes caused by periodic potential treatments: phenomenological approach

Abstract: The changes in surface structure of polyfaceted single crystal platinum spheres subjected to repetitive square-wave potential treatments in acid solution have been studied. The dependence of the prevailing type of change on symmetry, potential limits and frequency of the periodic potential has been determined. Results are discussed on the basis of different reactions occurring within definite potential windows and distinct rate controlling processes depending on the operating conditions. Accordingly, the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 34 publications
(43 reference statements)
1
52
1
1
Order By: Relevance
“…In addition, one should consider that, from procedures I and II, some electrochemical faceting of noble metals (platinum, palladium, ruthenium) by applying triangular periodic potential routines in aqueous acids also occurs [55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one should consider that, from procedures I and II, some electrochemical faceting of noble metals (platinum, palladium, ruthenium) by applying triangular periodic potential routines in aqueous acids also occurs [55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…1). This surface exhibits a high proportion of reaction sites equivalent to stepped planes of narrow (111) terraces (13,27). On the other hand, when a pc Pt electrode was subjected to a SSWPR between 0.05 and 1.50 V at 5.5 kHz for 5 min in the background solution, a new surface resulted in a high proportion of sites with narrow terraces of (100) planes (16,28) (Fig.…”
Section: Methodsmentioning
confidence: 94%
“…The application of potential periodic routines on noble metal electrodes produces either instantaneous or permanent morphological changes, depending on the characteristics of those routines. Fast symmetric potential perturbations applied to Pt electrodes in acidic media produce permanent changes in the morphology of the surface, that is, a new defined crystallographic orientation and/or a certain surface roughness (13,18). The electrochemical responses of the resulting interfaces are generally different from those of the initial ones and the electrocatalytic activities of the studied processes exhibit new interesting features (14 -18).…”
Section: Introductionmentioning
confidence: 98%
“…It has been found that the application of a PPP can produce dramatic changes on the morphology and crystallography of metal electrodes [8,10,11]. In the case of ferrous metals, there are some papers dealing with the effects of periodic potential programs [15,18].…”
Section: Electrochemical Surface Modifications Of Naval Steel Surfacementioning
confidence: 99%
“…Previous studies on noble electrodes in acid media have demonstrated the possibility of changing the distribution of the surface crystallography and surface roughness using these methodologies [8]. The application of these PPP on metal electrodes produces either temporary or permanent morphological changes, depending on the applied frequency and potential limits [9][10][11]. Thus, the application of a fast (larger than 2 kHz) symmetric PPP on noble metal electrodes in acid media develops new crystallographic planes without changes in the surface roughness [11,12].…”
Section: Introductionmentioning
confidence: 99%